Evaluation Of Protective Effect Of Delonix Elata On Chronic Inflammation And Comparison Of Its Ulcerogenic Potential With Ibuprofen. - K. MANIMEKALAI,; KARTIK J. SALWE,; HARSHA M. SHETTY, (International Journal of Pharma and Bio Sciences, 2011)
Antinociceptive property of ethanolic extract of plant Delonix Elata was screened by acetic acid induced writhing in mice while the anti-inflammatory property against chronic inflammation was studied using cotton pellet granuloma in rats. The gastric irritant action was tested by administering the drug orally and screening the gastric mucosa macroscopically and microscopically in rats. The severity of ulcers were scored from zero to five. Plant extract of Delonix elata, at the dose 100 and 200 mg/kg showed significant reduction in the number of writhing with 55.56% and 54.76% of inhibition respectively along with significant dose dependent reduction in the weight of cotton pellet from 48.7 mg to 31.3 mg and 28.5 mg respectively. The results were comparable to the standard drug, Ibuprofen. The histological section after administration of Ibuprofen indicated superficial erosion, in contrast to intact surface epithelium after treatment with D.elata.